CTA Gender strategy - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2014)
This strategy updates CTA’s first strategy on gender and agriculture published in 2003. Along with CTA’s Partnership and Youth Strategies it was developed to complement CTA’s Strategic Plan 2011-2015. It should therefore be read in conjunction with these. CTA’s Gender Strategy is built around three main areas of intervention: engaging women in inclusive value chains, increasing their participation in policy processes and building their capacity in ICTs and knowledge management. Each of these three areas will be addressed through a two-pronged approach. However, two main innovations of this strategy deserve particular mention.